Comparison of postoperative pulmonary complications between sugammadex and neostigmine in lung cancer patients undergoing video-assisted thoracoscopic lobectomy: a prospective double-blinded randomized trial - Tae Young Lee; Seong Yeop Jeong; Joon Ho Jeong; Jeong Ho Kim; So Ron Choi (Anesthesia and Pain Medicine, 2021)
Background Reversal of neuromuscular blockade (NMB) at the end of surgery is important for reducing postoperative residual NMB; this is associated with an increased risk of postoperative pulmonary complications (PPCs). Moreover, PPCs are associated with poor prognosis after video-assisted thoracoscopic surgery (VATS) for lobectomy. We compared the effects of two reversal agents, sugammadex and neostigmine, on the incidence of PPCs and duration of hospital stay in patients undergoing VATS lobectomy. Methods After VATS lobectomy was completed under neuromuscular monitoring, the sugammadex group (n = 46) received sugammadex 2 mg/kg, while the neostigmine group (n = 47) received neostigmine 0.05 mg/kg with atropine 0.02 mg/kg after at least the third twitch in response to the train of four stimulation. The primary outcome was incidence of PPCs. The secondary outcomes were duration of hospital stay and intensive care unit (ICU) admission. Results There was no significant difference in the incidence of PPCs for both the sugammadex and neostigmine groups (32.6% and 40.4%, respectively; risk difference = 0.08; 95% confidence interval = [−0.12, 0.27]; P = 0.434). The lengths of hospital (P = 0.431) and ICU (P = 0.964) stays were not significantly different between the two groups. Conclusions The clinical use of sugammadex and neostigmine in NMB reversal for patients undergoing VATS lobectomy was not significantly different in the incidence of PPCs and duration of hospital and ICU stay.